Incorporation of Li dopant into Cu2ZnSnSe4 photovoltaic absorber: Hybrid-functional calculations - Ghorbani, Elaheh; Mirhosseini, Hossein; Kiss, Janos; Felser, Claudia (Journal of Physics D: Applied Physics, 2015)
We have studied the formation of Li extrinsic defects in Cu2ZnSnSe4 by first-principles hybrid functional calculations. Li atoms in the Cu site (LiCu) and Li atoms in the Se site (LiSe) are the most and the least stable point defect, respectively. The formation energies of two Li interstitial defects with different numbers of nearest neighbors are the same. These interstitial point defects act as a donor but do not create gap states. Formation of the acceptor point defects (LiZn and LiSn) is less likely in p-type Cu2ZnSnSe4 compared with n-type Cu2ZnSnSe4. In contrast to LiZn which does not create gap states, the formation of LiSn creates two charge transition levels in the middle of the bandgap which might act as recombination centers. (Li-Li)Cu dumbbells are likely to form in p-type Cu2ZnSnSe4 but the probability of the formation of dumbbells decreases in favor of the formation of two LiCu point defects when the chemical potential of the electrons increases.
CRIS-Team Scopus Importer:2023-03-20
Keywords: CZTSe; Lithium; Photovoltaic